Association of Hematological and Lipid Profile Parameters with Respiratory Functions in Class I Obese Young Adults - Salah Uddin; Farhen Malik (Pakistan Journal of Medicine and Dentistry)
Background: Among the different forms of obesity, abdominal obesity has shown powerful associations with cardiovascular and respiratory issues. This study aimed to evaluate the association of hematological and lipid profile parameters with respiratory functions in Class I obese young adults.